Pengaruh Kualitas Produk, Citra Merek, dan Word of Mouth Terhadap Keputusan Pembelian BBM (Studi Kasus pada SPBU Vivo Tambun) - Nugraha, Revaldo Dwi; Andrian, Andrian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study was conducted to analyze the influence of product quality, brand image, and word of mouth on purchasing decisions for petroleum products at the Vivo Tambun gas station. Rising demand and competition among petroleum product providers have prompted companies to better understand the factors that influence consumers’ decisions when choosing products. This study employed a quantitative method, with data collected through a questionnaire distributed to consumers at the Vivo Tambun gas station. The sampling technique used non-probability sampling with a sample size of 100 respondents. Data analysis was performed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, and F-tests. The results indicate that product quality, brand image, and word-of-mouth have a positive and significant influence on purchasing decisions, both partially and simultaneously. Brand image is the most dominant factor influencing the decision because consumers consider the level of trust and the positive image of the Vivo gas station. Product quality contributes positively through good fuel performance that meets consumer needs. Additionally, positive word of mouth further reinforces consumers’ purchasing decisions. Collectively, these three variables explain 77.1% of the variation in purchasing decisions, while the remaining 22.9% is influenced by other factors. The Vivo Tambun gas station is expected to continue improving quality, strengthening its brand image, and optimizing its communication strategies to boost purchasing decisions and customer loyalty.